Short communication: Traditional medicinal plants and their uses from Sembirai Village, Kota Belud District, Sabah State, Malaysia Borneo - SAIDATUL NORNIS HJ. MAHALI; ROSMAH DERAK; ZALEHA A. AZIZ; BERNADETTE TOBI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mahali SNH, Derak R, Aziz ZA, Tobi B. 2023. Short communication: Traditional medicinal plants and their uses from Sembirai Village, Kota Belud District, Sabah State, Malaysia Borneo. Biodiversitas 24: 5956-5961. The Sama-Bajau of the Kota Belud District in Sabah, Malaysia, uses traditional medicine as an alternative to conventional medicine. However, this knowledge is at risk of disappearing because it has not been scientifically documented. The aim of this study was to identify the various traditional medicinal plants used to treat various common diseases. The primary data for this qualitative study was collected through semi-structured interviews, pictures, and observations. Two practitioners of traditional Sama-Bajau medicine were selected based on their role as skilled healers and their importance to the villagers during times of emergency. They were also chosen based on their reputation in their community and their vast knowledge of traditional herbs. Based on their interviews, 30 plant species from 22 families were identified as traditional medicines. The Arecaceae, Moraceae, and Zingiberaceae families are among the different herb families used by the Sama-Bajau. The simple treatment methods used by the healers involve the use of leaves, rhizomes, tubers, stems, bark, and fruits. There are various methods of preparing medicines, such as boiling, simmering, brewing, and chewing. The use of plants as traditional medicine is an important part of the indigenous knowledge of the Sama-Bajau society and holds great potential for future development.